2016
DOI: 10.1021/acs.iecr.6b03120
|View full text |Cite
|
Sign up to set email alerts
|

Melt-Miscible Oxalamide Based Nucleating Agents and Their Nucleation Efficiency in Isotactic Polypropylene

Abstract: In this study, the performance of three aliphatic oxalamide based compounds as nucleating agent (NA) for isotactic polypropylene (iPP) has been evaluated. The NAs evaluated in this study contain two oxalamide motifs that are connected through linking spacers with 2, 3, or 4 methylene units in between the oxalamide groups, while containing flexible hexyl end-groups on the outside. It is demonstrated that the onset of crystallization in the presence of these NAs under quiescent conditions, generally observed aro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 43 publications
3
36
0
Order By: Relevance
“… 31 For example, in previous work we demonstrated that shearing i PP systems blended with OXA3,6 increased the onset of crystallization from 123 to 140 °C, making it comparable to other organic nucleating agents such as the sorbitol derived nucleating agent DMDBS. 4 This synergetic effect between the nucleating efficiency of OXA 3,6 and shear is believed to be similar to that of sheared systems that contain (nucleating) nanoparticles. 15 , 19 , 32 36 In general, this synergy is attributed to the enhancement of the flow effect on the polymer kinetics and morphology.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“… 31 For example, in previous work we demonstrated that shearing i PP systems blended with OXA3,6 increased the onset of crystallization from 123 to 140 °C, making it comparable to other organic nucleating agents such as the sorbitol derived nucleating agent DMDBS. 4 This synergetic effect between the nucleating efficiency of OXA 3,6 and shear is believed to be similar to that of sheared systems that contain (nucleating) nanoparticles. 15 , 19 , 32 36 In general, this synergy is attributed to the enhancement of the flow effect on the polymer kinetics and morphology.…”
Section: Resultsmentioning
confidence: 80%
“…It has been earlier reported by us that the OXA3,6 nucleating agent crystals provide a surface for nucleation, which on shear alignment will provide the required orientation facilitating the transcrystallization morphology. 4 For this reason, we attribute the kebab crystal growth observed after the application of low γ̇ to the shear-alignment of the OXA3,6 crystals. A further increase in the L p to 22.7 nm is observed only after the application of a shear pulse with γ̇ ≥ 100 s –1 , indicating the presence of a shear-induced shish-kebab morphology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the self-assembly of OXA3,6 proceeds via a nucleation and growth mechanism, the resultant particle morphology is found to be strongly dependent on parameters such as the application of shear, concentration, and cooling rates (Figure 1C). 10,24…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only very few NAs are operational from commercial perspective. Frequent attempts have been made to explore the new structure NAs as well as to study the mechanism of heterogeneous nucleation . Bhatia et al reported that metal glycerolate platelets were highly effective NAs for iPP and the nucleation occurred epitaxially from platelet edges .…”
Section: Introductionmentioning
confidence: 99%